Contemporary regionalism and The Scandinavian 8 Million City: spatial logics in contemporary region-building processes. Issue 5 (4th May 2021) - Grundel, Ida
ABSTRACT: This paper shows how certain spatial logics are used to support contemporary region-building processes, and how these become taken for granted and institutionalized in specific regional settings. These spatial logics are also representative of the spatial logics dominating contemporary regionalism and affect the ways 'spaces' and 'citizens' are treated and valued in regional planning and policy. Few studies have shown how spatial logics are implemented, transformed and turned into policy across a wider set of regions. Exemplified by The Scandinavian 8 Million City project, the paper shows how this regional imaginary was constructed by the project promotors using several representative spatial logics of what constitutes the 'best' region as idealized in planning and policies.